Matching Well Test Data with Computer Model - Aljawad, Dr. Mohamed Saleh; Hlaeel, Dr. Mohamed; Dawood, Abdul-Mohaimin Abbas; Ali, Alya‘a Mahmood; Nsaeef, Hiba Ala‘a (Journal of Petroleum Research and Studies, 2017)
This project concerning with matching the well test data for one of Buzurgan wells the objective of make matching is to see if the observed data of the well test as same as the calculated one by using the mathematical model we made by using computer program. The well test data was available for matching was consist of three build up test two of them have a record for the well head pressure and bottom hole pressure and one just contain a record for the well head pressure so after matching we can make correlation to find the bottom hole pressure for the test haven‘t BHP values . By using Eclipse program we build a mathematical model for the well BU-6 The model consist of six layer (MA, MB11, MB12, MB21, MC1and MC2) and we take r=1, theta=10,we use the available data in Buzurgan field reports and then we enter the well test data and see the result of matching between the observed and the calculated one. From the matching we see that there was good matching between the two data, the matching was for the production and the bottomhole flowing pressure and the two was matched with the observed one. In order to make the matching very well we make change in permeability and increase its value by 20% and this change was very good to the matching of the production data and we also change the skin factor to -3.6 and that effect on the pressure matching and make it very well.